Inflation Targeting and Monetary Policy in Ghana. (15th May 2019) - Bleaney, Michael; Morozumi, Atsuyoshi; Mumuni, Zakari
Abstract: An inflation-targeting regime has been in place in Ghana since 2007, but the inflation rate has remained persistently high. During the 2007–2017 period, inflation exceeded the announced target by four percentage points on average, despite the target never falling below a relatively unambitious 8% per annum. We investigate whether the poor conduct of monetary policy is responsible for this outcome, and find that it is not. Monetary policy reaction functions are similar to those estimated for countries with successful monetary policies, and interest rates respond in the theoretically recommended way to inflation shocks.